2021
DOI: 10.3390/foods10112553
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Ultra-Processed Food Consumption and Lifestyle Behaviors Following COVID-19 Shelter-in-Place: A Retrospective Study

Abstract: Ultra-processed food (UPF) consumption poses a potential risk to public health and may be related to shelter-in-place orders. This study utilized the level of food processing as a lens by which to examine the relationships between diet, weight change, and lifestyle changes (including cooking, snacking, and sedentary activity) that occurred during regional shelter-in-place orders. This study used a cross-sectional, retrospective survey (n = 589) to assess baseline demographics, changes in lifestyle behaviors us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…This study revealed a high prevalence of mental disorder symptoms, given the high prevalence of symptoms of anxiety and depression in Brazilian adults during the COVID-19 pandemic. This prevalence may be explained by the fear of the disease and its implications for health, uncertainties about the spread of the virus and its treatment, the high mortality rates, and the loss of family members and relatives, in addition to the disruption of daily routines and lifestyles marked by the imposition of restrictive measures characterized by social distance ( 8 ), the restriction of physical and in-person trade ( 43 ), the decrease in physical activity during leisure time and the increase in sedentary behavior ( 44 , 45 ), increased alcohol consumption ( 46 , 47 ), a decreased purchase of fresh foods, and increased impulse buying ( 48 ), especially of ready-to-eat foods with high durability ( 49 , 50 ), characterizing health risk behaviors. Studies have shown that engaging in these behaviors, especially those related to comfort, may be a way for people to manage psychological distress and stressful situations ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed a high prevalence of mental disorder symptoms, given the high prevalence of symptoms of anxiety and depression in Brazilian adults during the COVID-19 pandemic. This prevalence may be explained by the fear of the disease and its implications for health, uncertainties about the spread of the virus and its treatment, the high mortality rates, and the loss of family members and relatives, in addition to the disruption of daily routines and lifestyles marked by the imposition of restrictive measures characterized by social distance ( 8 ), the restriction of physical and in-person trade ( 43 ), the decrease in physical activity during leisure time and the increase in sedentary behavior ( 44 , 45 ), increased alcohol consumption ( 46 , 47 ), a decreased purchase of fresh foods, and increased impulse buying ( 48 ), especially of ready-to-eat foods with high durability ( 49 , 50 ), characterizing health risk behaviors. Studies have shown that engaging in these behaviors, especially those related to comfort, may be a way for people to manage psychological distress and stressful situations ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings contribute to a growing body of research examining the effects of the COVID-19 confinement on health promotion behaviors. For example, in a cross-sectional, retrospective survey of 589 California Bay area adults, researchers found that increased snacking activity was strongly related to increases in ultra-processed food consumption and weight gain ( Sobba et al, Oct 23 2021 ) during shelter-in-place confinement. Furthermore, in a longitudinal study assessing changes in body weight and lifestyle behaviors in US adults (n=727) during the pandemic, Bhutani et al found that participants gained significant body weight (0.62 kg) during the pandemic and that those who gained weight engaged in riskier nutritional behaviors (i.e., more frequent snacking and alcohol intake) and were less active during the peak shelter-in-place (April/May 2020) and that these behaviors persisted after confinement ended.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research has demonstrated that almost 1 in 3 adults in the United States reported delaying or avoiding routine medical care because of COVID-19 concerns. ( Sobba et al, Oct 23 2021 ) This combination of decreased health promotion behaviors and decreased routine healthcare utilization that could promote screening may result in an increase in undiagnosed diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the influence of the COVID-19 pandemic on the reported intake could not be assessed. Some studies have reported that the COVID-19 pandemic has affected food consumption in certain populations [ 45 , 46 ], while other studies reported that food consumption remained largely the same [ 47 , 48 ]. As this study was conducted during the COVID-19 pandemic, an influence of the pandemic on the reported intake cannot be precluded.…”
Section: Discussionmentioning
confidence: 99%